General equilibrium pricing with information asymmetry - Zhang, Yuzhong; Dong, Fangfei (Frontiers in Applied Mathematics and Statistics, 2015)
We propose a general equilibrium model for asset pricing that incorporates asymmetric information as the key element determining security prices. In our setting, the concepts of completeness, arbitrage, state price and equivalent martingale measure are extended to the case of asymmetric information. Our model shows that in a so-called quasi-complete market, the agents with differential information can reach an agreement on an universal equilibrium price. The corresponding state price and martingale measure are determined. The key intuition is that agents evaluate consumption choices conditioned on their private information and the public information generated by price. As a consequence, information asymmetry can lead to mispricing as well.